The Impact of Using Audio Visual Media on Students' Learning Outcomes in English Grade VII of Junior High School - Resty Wahyuni; Khairun Nissa (English Teaching and Linguistics Journal (ETLiJ), 2023)
This study aims to determine The Impact of Using Audio-Visual Media on the English Learning Results of Grade VII of Sabilina Junior High School, Deli Serdang. This research is exploratory research in the form of a quasi-experimental design type non-equivalent control group design that employs a test group and a control group. The experimental group was treated using audio-visual media, while the control group using normal lecture method and printed book media. Information collection methods utilized English learning results tests and perception sheets. The information examination procedure employs the t-test to test the impact of utilizing audio-visual media on student learning results. The results show that the calculation of the normal post-test value of the test group is 82.25 which is higher than the normal control group which is 68.25. The results of the information examination appeared that the tcount 3,701 ttabel 1,729. This could be translated that learning uses audio-visual media has higher learning results compared to learning that does not utilize audio-visual media. To conclude, it appears that the use of sound media influences students' English learning results. After all, teachers ought to disseminate the utilization of audio-visual media in learning English to improve student learning results.